The Effect Of Financial Distress Of The Altman, Springate, And Zmijewski Models On Stock Returns Of Indonesian Transportation Issuers In 2016-2020 - Putra, Abdi; Ananto, Rangga Putra; Heriyanto, Randy (Devotion : Journal of Research and Community Service, 2021)
Financial distress is a condition where the company is unable to fulfill its obligations. This is usually accompanied by consecutive negative earnings. The transportation sector is one sector that is vulnerable to experiencing financial distress. This is due to the many new, more innovative competitors. As well as regulatory policies that are not in favor of this industry. Therefore, the burden borne by the company is not proportional to the income earned, resulting in financial difficulties. To measure this financial distress, the author uses several models such as: Altman model, Springate model, and Zmijewski model. This study examines the effect of financial distress from each of these models on stock returns. The data used in this study comes from financial reports and other financial data for the period 2016-2020. The results showed that there was no significant effect of the Altman, Springate, and Zmijewski models of financial distress on stock returns in this sector.